An Analysis of the Use of Visual Teaching Aids in Stimulating Students’ Questioning Skills in IPAS Learning in Grade V at SD Negeri 06 VII Koto Sungai Sarik - Lisa, Elvina; Azwar, Rica; Efrina, Gusnita; Oktira, Yona Syaida (The Future of Education Journal, 2025)
This research motivated by the low questioning skills of students in IPAS learning, which is still dominated by the lecture method. Student tended to be passive and rarely asked questions, making the learning process less interactive. The aim of this study was to describe the use of visual teaching aids in IPAS learning and to analyze how these media can stimulate the questioning skill students. This study employed a qualitative method with a descriptive approach. The research subjects were the teacher and fifth-grade students of SD Negeri 06 VII Koto Sungai Sarik. Data were collected throught observation, interviews, and documentation, then analyzed descriptively through data reduction, data display, and conclusion drawing. The result showed that the use of visual teaching aids helped the teacher explain abstract concepts into more concrete ones, attracted students attention, and fostered curiosity. Visual media were also proven to stimulate students questioning skills, both in terms of the quantity and quality of questions asked. However, the limited facilities at school made the use of visual aids inconsistent in every learning session.